Pembangunan Aplikasi Transaksi Menu Di Kedai XYZ Kopi Menggunakan QR-Code Dan One Time Password Berbasis E-Wallet - Fazri Muhamad Kurnia; Irawan Afrianto (Matrix : Jurnal Manajemen Teknologi dan Informatika, 2020)
The payment process using electronic money is a non-cash payment method based on E-Wallet aimed at facilitating users in transact. The transaction process at the coffee shop XYZ is still done conventionally and takes a long time, causing long queues. The research carried out aims to speed up the transaction process at XYZ coffee shops. The method used in this research is prototype. An alternative solution to the transaction process is to utilize the E-Wallet and QR-Code through the customer's smartphone. This study utilizes Go-Pay E-Wallet access as a means of payment through the Midtrans Payment Gateway and uses the One Time Password code as a login method on the system. Qr-code scanning to place orders can be done quickly which is around 3,551 milliseconds. Quessioner results distributed to 20 customers showed the following data, around 90% agreed on the use of e-wallet as an alternative payment, around 87% agreed on the statement of the use of e-wallet was able to reduce the slow transaction process, about 79% agreed to the statement that this system facilitates the transaction process, as well as 79% level of approval of the use of an authentication code through a mobile number that makes it easy to enter the application. The results showed that the system built can speed up the transaction process.